Push-out bond strength of glass fiber posts with two universal adhesives in endodontically-treated teeth - A Valian; M Maghsoudlou; MS Roudbari (Islamic Azad University, 2021)
Objectives: Attempts are ongoing to simplify the bonding procedure by decreasing the procedural steps. Universal adhesives were introduced to serve this purpose. This study aimed to evaluate the push-out bond strength of glass fiber posts in endodontically-treated teeth with two universal adhesives.  Materials and Methods: In this in vitro, experimental study, 22 single-rooted mandibular premolars were decoronated at their cementoenamel junction, endodontically treated and were randomly divided into two groups. The G-Premio Bond was used in the first and All-Bond Universal was used in the second group, according to the manufacturers' instructions. Angelus fiber posts were cemented using RelyX U200 Automix self-adhesive resin cement. The roots were cut into 1-mm-thick sections perpendicular to the longitudinal axis of the tooth in the cervical, middle, and apical thirds. The push-out test was performed in a universal testing machine at a crosshead speed of 1 mm/min, and bond strength values were recorded. The failure modes were also determined. The data were analyzed using ANOVA and linear mixed models. Results: The mean push-out bond strength was significantly higher in All Bond Universal than G-Premio Bond (P=0.036). Also, there were statistically significant differences in the push-out bond strength of adhesives in different parts of the root canal (P=0.039). All failures were type 4 in both groups (adhesive failure between the dentin and resin cement). Conclusion: All Bond Universal yielded superior push-out bond strength than G-Premio. However, further in vitro and in vivo studies with larger sample size are required for an evidence-based decision making.